VIBRO-MAGNETIC-ABRASIVE PROCESS SUPER HARD CERAMICS - Бурлаков, Виктор (SWorldJournal, 2021)
The article touches upon the problem of processing super hard ceramics in connection with its use as cutting inserts and proposes a method by which such a problem can be solved. Both the process of removing the chips and the location of the cutting tool